Search for Correlations of High-energy Neutrinos Detected in IceCube with Radio-bright AGN and Gamma-Ray Emission from Blazars - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, Juan A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Astrophysical Journal, 2023)
The IceCube Neutrino Observatory sends realtime neutrino alerts with a high probability of being astrophysical in origin. We present a new method to correlate these events and possible candidate sources using 2089 blazars from the Fermi-LAT 4LAC-DR2 catalog and with 3413 active galactic nuclei (AGNs) from the Radio Fundamental Catalog. No statistically significant neutrino emission was found in any of the catalog searches. The result suggests that a small fraction, <1%, of the studied AGNs emit neutrinos that pass the alert criteria, and is compatible with prior evidence for neutrino emission presented by IceCube and other authors from sources such as TXS 0506 + 056 and PKS 1502 + 106. We also present cross-checks to other analyses that claim a significant correlation using similar data samples.
CRIS-Team Scopus Importer:2023-10-20